2015
DOI: 10.2507/ijsimm14(3)5.295
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Modified Low-Density Jet Penetrating Shell Charge

Abstract: In order to solve the problem of inadequate penetration of low-density jet penetrating shell charge, the low-density PTFE are modified by adding a certain fraction of copper powder in the matrix. This treatment helps to increase the material density and jet energy, as well as to improve the static and dynamic mechanical properties of the material. AUTODYN-2D finite element software is used to simulate the process in which the low-density jet forms and penetrates shell charge. The simulation and experiment resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 6 publications
0
22
0
2
Order By: Relevance
“…In general, PTFE-based reactive materials are formed by mixing active metal powders within the fluoropolymer binder and then are consolidated via a pressing/sintering process, such as PTFE/Al [1,2], PTFE/Ti [3], and PTFE/Cu [4]. These reactive materials are a class of energetic materials that are formulated to release their chemical energy under intense dynamic loadings or high pressures and high strain rates [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, PTFE-based reactive materials are formed by mixing active metal powders within the fluoropolymer binder and then are consolidated via a pressing/sintering process, such as PTFE/Al [1,2], PTFE/Ti [3], and PTFE/Cu [4]. These reactive materials are a class of energetic materials that are formulated to release their chemical energy under intense dynamic loadings or high pressures and high strain rates [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies on reactive liner shaped charges indicated that the reactive material mass entering the penetration hole and the initiation location of the reactive jet significantly influenced the overpressure inside the targets or the damage mechanism of concrete and steel targets [22,23,24]. In addition to PTFE/Al reactive materials, the jet formation and penetration behaviors of PTFE and PTFE/Cu reactive liner shaped charges have also been researched by experiments and simulations [4,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Reactive material liner is a kind of integrated solid energetic liner prepared by filling metal powders in a high polymer binder, typically such as polytetrafluoroethylene (PTFE)/Al and PTFE/Cu, and then fabricating by a cold pressing and sintering process [1,2]. Generally, the reactive material liner under the shaped charge effects can form a reactive jet with high velocity to penetrate the target and then release its violent chemical energy inside the penetration crater, resulting in extremely large amounts of damage to concrete or geologic material targets [3].…”
Section: Introductionmentioning
confidence: 99%
“…The penetration behaviors of PTFE/Al reactive jets against thick steel plates under different standoffs were studied, and the experiments showed that the fragmentation effects of penetrated steel plates were produced at the standoff of 0.5, 1.0, and 1.5 CD (charge diameter), whereas the penetration depths were only approximately 1.0 CD [9,10]. Yin et al and Wang et al compared and analyzed the penetration performance of a PTFE jet and PTFE/Cu jet impacting shell charge and main armor by simulations and experiments combined, and the results verified that the penetration capability of the PTFE/Cu jet increased to some extent [2,11]. In addition to PTFE-based reactive material liners, metal powders reactive liners have been widely studied in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Chang, B.H. et al [12] enhanced the penetration depth for low density jet by 5.38 % adding a certain fraction of copper powder in the matrix.…”
Section: Introductionmentioning
confidence: 99%